2022
DOI: 10.1186/s12871-022-01710-9
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and effectiveness of ultrasound combined with nerve stimulator-guided lumbosacral plexus block in the supine versus lateral position during surgeries for lower limb fracture-a prospective randomized controlled trial

Abstract: Background Patients with lower limb fracture often have acute pain and discomfort from changes in position, and such pain affects early postoperative recovery. This study aimed to compare the applicability and effectiveness of ultrasound combined with nerve stimulator-guided lumbosacral plexus block (LSPB) in the supine versus lateral position during lower limb fracture surgery. Methods We included 126 patients who underwent elective internal fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A randomized controlled trial that included a total of 126 patients showed that supine-position lumbar plexus nerve block can achieve good analgesic effects. Compared to lateral lumbar plexus nerve block, patients undergoing supine-position lumbar plexus nerve block have higher satisfaction, better nerve identification and localization, shorter procedure times, and a lower risk of epidural blockade, making it a safer and more convenient approach [54].…”
Section: Lower Limb Injuriesmentioning
confidence: 99%
“…A randomized controlled trial that included a total of 126 patients showed that supine-position lumbar plexus nerve block can achieve good analgesic effects. Compared to lateral lumbar plexus nerve block, patients undergoing supine-position lumbar plexus nerve block have higher satisfaction, better nerve identification and localization, shorter procedure times, and a lower risk of epidural blockade, making it a safer and more convenient approach [54].…”
Section: Lower Limb Injuriesmentioning
confidence: 99%